Implementasi Corporate Social Responsibility PT. Bayan Resources Tbk Berdasarkan SEOJK. No.16/SE.OJK.04/2021 - Ika Makherta Sutadji; Nina Indriastuty; Nely Tangke Rante (Yayasan Almanar Pujud, 2024)
The purpose of this research is to provide information and understanding regarding the implementation of Corporate Social Responsibility (CSR) reporting in the Sustainability Report. This research was conducted to understand the things that have done by the company and disclosed in the Sustainability Report in carrying out the CSR Program. The subject of this research is PT. Bayan Resources Tbk. using the 2021 Sustainability Report. This Sustainability Reports the first report to be made because it refers to the provisions of the Indonesian government as outlined in the SEOJK. No. 16/SE.OJK.04/2021. The research method used in this research is descriptive qualitative. The conclusion from the result of this study PT. Bayan Resources Tbk. has strived to meet Indonesian government standards. The practices that have been carried out so far have reflected CSR activities and have not been included in the Sustainability Reports. PT. Bayan Resources Tbk has carried out practices that are beneficial to the environment and society in the long term to contribute to Indonesia’s Sustainable Development Goals.